Fucosidosis with Dystonia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
A Canadian male child with fucosidosis and dystonia is reported from the Department of Biochemical Genetics, University of Western Ontario, London, Ontario, Canada.